Diagnostic Value of Serum Neuron-Specific Enolase Level in Patients With Acute Ischemic Stroke; A Systematic Review and Meta-Analysis - Najmi, Elham; Bahbah, Eshak I.; Negida, Ahmed; Afifi, Ahmed M.; Baratloo, Alireza (International Clinical Neuroscience Journal, 2019)
Background: We aim to assess the predictive value of serum neuron-specific enolase (NSE) level in patients with acute ischemic stroke referring to the emergency department. Methods: This systematic review and meta-analysis performed, considering the PRISMA and MOOSE statement guidelines. A computerized literature search of the known medical database conducted by using the relevant keywords. We included studies published before November 2016 in which stroke patients compared with non-stroke controls and also studies evaluating the serum levels of NSE in the study groups. Statistical analysis was pooled in a random effect model analysis using the Comprehensive Meta-Analysis software. Results: We included 12 articles in the qualitative and quantitative analysis, that their quality acceptable based on the Newcastle Ottawa Scale (NOS scale). The pooled effect estimates showed that NSE is significantly higher in ischemic stroke patients in comparison with their controls with a high effect estimate [OR 9.68, 95% CI (3.06 to 30.6)]. The effect estimate remained statistically significant under the fixed and random effects model. Conclusion: Our results show higher levels of NSE in patients with stroke than in the control group, indicating that NSE plays a role in the diagnosis of stroke. In terms of prognosis, there is evidence regarding the direct and indirect relationship; and it founded that serum levels of NSE is higher in larger stroke volume, which needs further research.